PENGARUH PEMBELAJARAN MODEL 4D TERHADAP HASIL BELAJAR MAHASISWA PROGRAM STUDI PPKN UNIVERSITAS AL ASYARIAH - Suhaeba Nur (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2012)
The purpose of this study is to determine how learning influences 4D models ( define, design , develop and dessiminate ) on learning outcomes of students CIVICS CIVICS Prodi Unasman first half . This type of research is experimental research . The population is all students of the 1st semester of Academic Year 2012-2012 Prodi PPKn as many as 61 students . Sampling with random sampling technique to select a class that is a class IA experiment as many as 31 students were on grade control is the IB grade 30 students . Instrument which is used in this study is test , interview guidelines and lembr observation . The results showed a significant difference in learning outcomes Students who received Civics on learning through 4D method ( define, design , develop and dessiminate ) obtain better learning outcomes than students who received learning through 4D method ( define , design , develop and dessiminate ) . It is based on research results of Ho is rejected because the t value is not in a position between the table and the t value is greater than the table value of t ( t count > t table ) . Positive t value ie value t = 10,873 and t table value = 2.66 ( 5 % ) and 2.39 ( 1 % ) , means that the average value of the group posttest experimental class higher than the class average posttest control . Based on the analysis results of the t test and the significance of the above , then Ho is rejected, which means that there is a positive and significant difference in the effect of the use of 4D learning model ( define, design , develop and dessiminate ) model with a lecture on learning outcomes of students of the first semester of Civics Prodi PPKn Unasman.